Remote Monitoring System for a Three-phase Electric Power Grid - Rujoi, Adrian-Mihai; Nan, Adriana-Georgiana; Kertész, Csaba Zoltán (IEEE, 2021)
This paper presents a solution for the remote monitoring of a three-phase electrical power grid. The solution is made up of three main parts: the data acquisition module which, at its core, has an ADE7758 integrated energy meter and uses a LoRa module for data transmission, the gateway which receives the data sent by the data acquisition module and sends it further to the database and the web application written in PHP, which interprets and displays the collected data. The presented solution was tested in various power measurement scenarios including long-term reliability check in a public lighting network. It also easily integrates into many kinds of low-voltage power networks and proved to be a very cost-effective and reliable alternative to other similar smart energy monitoring systems.
Keywords: remote monitoring; power grid; ADE7758; LoRa; IoT; gateway